2022
DOI: 10.1007/s00371-022-02431-3
|View full text |Cite
|
Sign up to set email alerts
|

Learning the shape of female breasts: an open-access 3D statistical shape model of the female breast built from 110 breast scans

Abstract: We present the Regensburg Breast Shape Model (RBSM)—a 3D statistical shape model of the female breast built from 110 breast scans acquired in a standing position, and the first publicly available. Together with the model, a fully automated, pairwise surface registration pipeline used to establish dense correspondence among 3D breast scans is introduced. Our method is computationally efficient and requires only four landmarks to guide the registration process. A major challenge when modeling female breasts from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…3) from affecting the model. The segmented torso region might still be affected by pose-related variations arising from presence of quasisimilar postures [30]. The choice of cylindrical template was inspired by previous studies [31], [32], which used either cylinders or truncated cones as part of the template to model the human shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) from affecting the model. The segmented torso region might still be affected by pose-related variations arising from presence of quasisimilar postures [30]. The choice of cylindrical template was inspired by previous studies [31], [32], which used either cylinders or truncated cones as part of the template to model the human shape.…”
Section: Discussionmentioning
confidence: 99%
“…The compactness of the model, which was developed using all the 225 scans, was defined as the ratio of the total variance explained by the principal vectors. The generalization error was calculated using leaveone-out cross-validation for all the 225 scans [30] and the specificity was calculated as the average minimum distance of uniformly distributed, randomly generated scans (n=100) from the training set (n=225) [29].…”
Section: Statistical Modelling Of Shape Variationsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Three-dimensional imaging devices recently emerged to allow objective quantification of disparity in projection, volume, and surface symmetry in various medical conditions. [14][15][16][17] Despite its tremendous potential, 3D surface imaging has not been applied in hand surgery to this point. Nevertheless, previous studies demonstrated the capability of patients to precisely outline the border of the AA precisely after digital-nerve repair.…”
Section: Discussionmentioning
confidence: 99%